Economic development, inequality and war : humanitarian emergencies in developing countries - Nafziger, E. Wayne; Auvinen, Juha. (New York : Palgrave Macmillan, 2003)
"Economic Development, Inequality, and War shows how economic decline, income inequality, pervasive rent-seeking by ruling elites, political authoritarianism, military centrality and competition for mineral exports contribute to humanitarian emergencies, a human-made crisis in which numerous people die from war and state violence. Economic regress and political decay bring about relative deprivation, and the perception by social groups of injustice arising from a growing discrepancy between what they expect and get. Nafziger and Auvinen's evidence indicates that both greed and grievance drive contemporary civil wars. Finally, the authors also identify policies, for preventing humanitarian emergencies."--BOOK JACKET.
Map: Countries experiencing humanitarian emergencies in the 1990s -- 1. A Humanitarian Emergency: War, Genocide, and Displacement -- Appendix to Chapter 1: Sources, Indicators, and Statistics -- 2. Poverty, Stagnation, Unemployment, and Inflation -- 3. Ethnicity, Political Economy, and Conflict -- 4. Inequality, Exclusivity, and Relative Deprivation -- 5. Stagnation, Inequality, Adjustment, and Elite Interests -- 6. Authoritarianism, Democratization, and Military Centrality -- 7. The Failure of Agriculture: Food Entitlements, Elite Violence, and Famines -- 8. The Conflict over Land and Natural Resources -- 9. Preventing Humanitarian Emergencies: Policy Implications.
Includes bibliographical references (p. 209-230) and index.
Keywords: War -- Economic aspects -- Developing countries -- Case studies; Disasters -- Economic aspects -- Developing countries -- Case studies; Poverty -- Political aspects -- Developing countries -- Case studies; Social conflict -- Economic aspects -- Developing countries -- Case studies; Profiteering -- Developing countries -- Case studies; War -- Economic aspects -- Developing countries -- Econometric models; Developing countries -- Economic conditions -- 21st century -- Case studies; Developing countries -- Economic conditions -- 21st century -- Econometric models